Helix Channel Microfluidic Electrophoresis Chip Drove by Low Voltage. (2017) - Li, Jiechao; Yan, Weiping; Lv, Hongfeng
Abstract: The conventional microfluidic electrophoresis chip must be applied higher voltage, which limited the microminiaturization and integration. According to the principle of electrophoresis chip, a helix channel electrophoresis chip drove by low voltage was proposed. Some key techniques were researched, which include the bubble issue, optimization of the chip structure, low cost hydrophilic surface modification for the chip, design of miniaturized control and detection system. Test results shown the helix channel chip has better separation than the cross channel chip, and the sample can be successfully separated below 100 V voltage.